Introduction: The Intersection of Religion with Radicalization and De-Radicalization Processes in Comparative Perspective - Medda-Windischer, Roberta (Religions, 2024)
Radicalization continues to be considered a contentious concept with little consensus on what categorizes a movement or individual as “radical” (or extreme) [...]